2019
DOI: 10.1088/1555-6611/aaf643
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of coupled nano-mechanical resonators in the weak optomechanical coupling regime

Abstract: Coupled nano-mechanical resonators (NRs) have recently attracted great attention for both practical applications and fundamental studies. As a preparation step, it is needed to cool the coupled NRs to their ground states. In this paper, we investigate the coupled mechanical resonators cooling by employing the covariance approach in the weak optomechanical coupling regime. We show that the optimum cooling results can be obtained simultaneously when the two NRs have identical frequency. In addition, using numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…On the other hand, when |G| κ, the system is in the strong-coupling regime, where normal-mode splitting occurs and the phonon occupancy exhibits Rabi-like oscillation with reversible energy exchange between optical and mechanical modes, it will bring about swap heating, which leads to the saturation of cooling rates. In our previous publication, we study the coupled mechanical resonators cooling in the weak optomechanical coupling regime [32]. In this paper we extend our previous results and present a detailed exploration of the cooling dynamics and cooling limits in the strong optomechanical coupling regime, where the light-enhanced optomechanical coupling strength |G| is far greater than the cavity decay rate κ.…”
Section: Introductionsupporting
confidence: 62%
“…On the other hand, when |G| κ, the system is in the strong-coupling regime, where normal-mode splitting occurs and the phonon occupancy exhibits Rabi-like oscillation with reversible energy exchange between optical and mechanical modes, it will bring about swap heating, which leads to the saturation of cooling rates. In our previous publication, we study the coupled mechanical resonators cooling in the weak optomechanical coupling regime [32]. In this paper we extend our previous results and present a detailed exploration of the cooling dynamics and cooling limits in the strong optomechanical coupling regime, where the light-enhanced optomechanical coupling strength |G| is far greater than the cavity decay rate κ.…”
Section: Introductionsupporting
confidence: 62%
“…Different from the classical properties of the mechanical systems at room temperature, the quantum properties of the mechanical systems are presented only at sufficiently low temperatures where the thermal fluctuations are suppressed. To suppress the thermal fluctuations of the mechanical systems and study their quantum properties, various ground-state cooling schemes have been proposed, such as cooling with dissipative coupling [25,26], quadratic coupling [27,28], resolved sideband cooling [29][30][31][32], the feedback cooling [33,34], including coherent feedback [35], cooling with static electrical interaction without any auxiliary qubit or photonic systems [36], hot thermal light cooling [37], time-dependent control cooling [38], measurement-based cooling [39], dynamic dissipative cooling [40], and quantum cooling in the strong [41] and weak [42] optomechanical-coupling regime. Experimentally, efficient cooling of a MR with high frequency ω m ≃ 2π × 6 GHz down to the ground state (with an average phonon number ⟨n⟩ ≃ 0.07) was achieved with a direct refrigerator of 25 mK [43].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, optomechanical mechanics [1][2][3] and electromechanical mechanics [4][5][6] have developed rapidly, it is expected that many quantum effects in macroscopic material structures can be observed in these systems, such as quantum information conversion [7,8], regular mode splitting [9], optomechanically induced transparency [10,11], slow light [12], frequency conversion [13], etc. In addition, experiments in both microwave and optical fields have demonstrated that the NAMR can be cooled to the ground state of vibration [14,15] and operate in a strong coupling range [16,17]. Therefore, it is possible to use the interaction between phonon-photons to realize the energy * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%